Artificial Intelligence Aided Physics Teaching : (An Experimental Study on the Development of Artificial Intelligence in Teaching Physics at the School level) - Bhat H R, Suresh (Educational Trend (A Journal of RIE, Ajmer - NCERT), 2025)
Students like to study Physics when there is creative approach. My teaching experience the students also tells a student doesn’t like to read lengthy lessons and theories. So, it is a strong belief that as far as possible discovery and experimental method with gadgets to be done. So, my experimental study is on the development of Artificial Intelligence Aided Teaching of Physics. After dividing the 9th and 10th standard students in to 2 groups of mixed abilities such as high achiever, mediocre and low achiever, provided the traditional group with questionnaire in Physics concepts which they have to solve by pen and paper without using any technology aids. Experimental group was provided with Artificial Intelligence aids such as Google assistant, Navigation app, Chatbots, Text editor and auto correct, Face recognition apps. When the analysis of the answers provided by the control group and the experimental group, it was noticed that the answers provided by experimental group was more practical and having realistic life experiences. The A I aid they have used to learn and answer the physics questions helped them to be more research oriented and to get the precision in defending their answers.